The dragon's eye - Chadda, Sarwat (Spirit animals. Fall of the beasts, 2018)
After being smuggled to a remote palace, four young Greencloaks and their spirit animals discover someone has been manipulating Erdas's leaders to uncover a relic believed to have the power to flood the world.